Quality planning in Construction Project - Othman, I. (Institute of Physics Publishing, 2018)
The purpose of this paper is to investigate deeper on the factors that contribute to the effectiveness of quality planning, identifying the common problems encountered in quality planning, practices and ways for improvements in quality planning for construction projects. This paper involves data collected from construction company representatives across Malaysia that are obtained through semi-structured interviews as well as questionnaire distributions. Results shows that design of experiments (average index: 4.61), inspection (average index: 4.45) and quality audit as well as other methods (average index: 4.26) rank first, second and third most important factors respectively. Â© Published under licence by IOP Publishing Ltd.